An assessment of deterioration in cultural heritage: the unique case of Eflatunpınar Hittite Water Monument in Konya, Turkey - Bozdağ, A.; İnce, İ.; Bozdağ, A.; Hatır, M. E.; Tosunlar, M. B.; Korkanç, M. (Springer Verlag, 2019)
Stone monuments are important symbols of cultural heritage of countries. However, many environmental factors negatively affect these monuments. The increasing damage on the stone monuments and the danger of irreversible loss of cultural heritage have resulted in growing efforts for the preservation of the monuments. Eflatunpınar Hittite Water Monument in Beyşehir, Konya, Turkey, is a unique Hittite cultural monument that has survived for nearly 3200 years even though it has been exposed to many environmental effects. In this study, non-destructive testing (NDT) was used to detect the degradation on the building stones of the Eflatunpınar Hittite Water Monument and change-deterioration maps were prepared subsequently. It was also investigated whether the chemistry of the Eflatunpınar spring water may cause deterioration. Additionally, the petrographic, chemical, and physico-mechanical properties of the rocks taken from the ancient stone quarry were determined in order to compare with the properties of the monument’s building stones. Based on the physico-chemical characteristics of the Eflatunpınar spring water and XRD results of crusts in building stone surface of the monument, it was identified that water can be effective on the formation of calcite and gypsum crusts especially in the lower parts of the monument. However, applied NDT methods and change-deterioration maps indicated that the deterioration as well as neglect and abandonment in the monument are mostly associated with the capillary effect of the flowing water through the structure and the deterioration effect is more apparent in contact points between the building stone and the flowing water. Additionally, in the building stones above the capillary front, the conservation condition is significantly better. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Building stone; Deterioration; Eflatunpınar Hittite Water Monument; Non-destructive tests; Physico-mechanical properties